Pengembangan E-Modul Buku Kesehatan Ibu dan Anak untuk Meningkatkan Pengetahuan Ibu - Yully Asmariana (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Services in the health sector have indirectly undergone changes, initially promotions could be in the form of face-to-face, now becoming a digital system called the industrial revolution 4.0. People in this world have been exposed to the digital system, so where there is a medium there must be a human. This change has a positive impact where you can enjoy this change. In the present era, it has developed into electronics in the form of modules, books (e-modules, e-books) and others. Development occurs in the book on maternal and child health (the MCH handbook). Methods in solving this problem can be done in stages include; (1) Dissemination of e-module links, (2) Mother's identity; (3) Pre test; (4) Learning (electronic); (5) Test post; (6) Personal or group discussion. Evaluation of the stages above, the process of developing the MCH e-module and the final result through the assistance of mothers who became respondents. By differentiating the initial and final results of learning, it is hoped that it will motivate mothers to carry out supporting activities for maternal and child health. In addition to the material, it can also be used as a reminder that mothers should check their mothers and children on time. With the development of this MCH handbook, it is hoped that mothers can wisely carry out pregnancy checks, preparation for birth to care and growth and development of children.